The Effects of an R103Q Mutation on the Chemical and Physical Properties of the Enzyme Cytochrome C Nitrite Reductase (ccNiR) - (:unkn) unknown (My University, 2022)
Cytochrome c Nitrite Reductase (ccNiR) is a periplasmic homodimeric decaheme enzyme that catalyzes the reduction of nitrite to ammonium in a process that involves six electrons and eight protons. The project described herein explored the properties of the Shewanella oneidensis R103Q ccNiR variant and compared them to the properties of the wild type enzyme. Under standard assay conditions, which use the strong reducing agent methyl viologen monocation radical (MVred) as an electron source, the R103Q variant still catalyzes reduction of nitrite to ammonium, albeit with an MVred turnover rate that is 20% of the wild type’s (780 ± 50 s-1 vs 4510 ± 90 s-1 for the wild type). Unlike the H257Q ccNiR variant described in an earlier study, R103Q’s MVred turnover rate was the same whether the electron-accepting substrate was nitrite or hydroxylamine (H257Q ccNiR’s MVred turnover rate is almost zero when nitrite is the electron acceptor but approaches that of the wild type when reducing hydroxylamine). The mechanistic implications of this observation are discussed. Nitrite-loaded R103Q ccNiR’s behavior under weakly reducing conditions differs substantially from that of the wild type, though it is still capable of catalyzing reduction of nitrite to nitric oxide when N,N,N,N-tetramethyl-p-phenylenediamine (TMPD) or hexaammineruthenium(II) (RuII) is the electron donor (the nitric oxide turnover rate is higher when the stronger RuII reductant is used). Regardless of the weak reductant used, a reduced R103Q ccNiR species with a characteristic UV/Vis absorbance spectrum is generated in an exponential process, with a half-life of about 30 minutes; the species is generated somewhat faster when pure RuII is the electron donor than when the weaker TMPD is used. A species with very similar UV/Vis spectra is seen when H257Q is reduced under mild conditions. On the other hand, when the nitrite-loaded wild type ccNiR is reduced under mild conditions (applied potentials above 0 mV vs SHE), the nitrite-loaded active site is converted to a species that has been identified as the 2-electron reduced {FeNO}7; this species has a substantially different UV/Vis spectrum from that obtained when R103Q or H257Q are reduced. When 400 M pure RuII is used as the electron donor to reduce nitrite-loaded R103Q ccNiR, UV/Vis stopped-flow studies show that one of the bis-His ligated low-spin hemes is reduced on the millisecond timescale (t0.5 ~ 20ms) and before the active site, which reduces with a half-life of about 1s to generate an active site species that is tentatively assigned as [FeH1II(NO2)]; that is, a ferrous heme with nitrite as axial ligand. The remaining ferrous bis-His ligated heme is exponentially re-oxidized with a half-life of ~120s, after which the active site slowly evolves to the species with distinctive UV/Vis spectrum described above. This species may be a non-catalytic form of the active site, in which case a major role of the residues R103 and H257 may be to prevent its formation.